The Rhetoric of Romans : argumentative constraint and strategy and Paul's dialogue with Judaism - Elliott, Neil. (Sheffield : JSOT Press, 1990)
We increasingly recognize that Paul did not write his letter to the Romans primarily out of doctrinal concerns. Paul B. Fowler presses that insight home in this attentive, yet eminently readable, study of the letter's structure. The principles of Fowler's reading are that rhetorical questions in Romans 3--11 structure the argument, not as responses to criticism but as Paul's careful guiding of the reader, and that these chapters, like the paraenesis in Romans 12--15, address specific circumstances in Rome. Careful attention to the rhetorical structure of the letter points to tensions between Jew and Gentile that aggravate the already precarious situation of the Roman congregation. In the course of his argument, Fowler explodes the common conceptions that Paul employs diatribal technique to answer objections and that he is primarily engaged in a debate with Jews. In short, Fowler demonstrates that the apostle is not writing defensively, but responding with sensitivity to the volatile atmosphere caused by Claudius's expulsion of some Jews from Rome. The book includes an appendix on rhetorical devices and another on epistolary formulas in Paul's letters.
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Criticism, interpretation, etc